Pendapat Sivitas Akademika tentang Pengembangan Kreativitas Menghadapi Tantangan Globalisasi di Perguruan Tinggi - Yumiati Suharto (Ilmu Pendidikan: Jurnal Kajian Teori dan Praktik Kependidikan, 2000)
Opinions of Academic Members about Creativity Development in Facing Challenges of the Globalization Era. The purpose of the study was to obtain empirical data concerning the opinions of academic members about creativity development in facing challenges of the globalization era. The data were collected from students, lecturers and administrators of the six teacher colleges in Jakarta by using a questionnaire and then analyzed statistically using chi square. The results indicate that there is no significant difference in terms of opinions about creativity development in facing globalization era between students, lecturers, and administrators. Most of them seemed to agree on the importance of creativity.